Extranodal NK-/T-cell lymphoma, nasal type: what advances have been made in the last decade? - Costa, Renata de Oliveira; Pereira, Juliana; Lage, Luís Alberto de Pádua Covas; Baiocchi, Otávio César Guimarães (Frontiers in Oncology, 2023)
Extranodal NK-/T-cell lymphoma (ENKTCL) is a rare and highly aggressive malignancy with significant racial and geographic variations worldwide. In addition to the formerly “nasal-type” initial description, these lymphomas are predominantly extranodal in origin and typically cause vascular damage and tissue destruction, and although not fully understood, Epstein–Barr virus (EBV) has an important role in its pathogenesis. Initial assessment must include a hematopathology review of representative and viable tumor areas without necrosis for adequate immunohistochemistry studies, including EBV-encoded small RNA (EBER) in situ hybridization (ISH). Positron emission tomography with 18-fluorodeoxyglucose (18F-FDG-PET/CT) for accurate staging is essential, and most patients will have localized disease (IE/IIE) at diagnosis. Apart from other T-cell malignancies, the best treatment even for localized cases is combined modality therapy (chemotherapy plus radiotherapy) with non-anthracycline-based regimens. For advanced-stage disease, l-asparaginase-containing regimens have shown improved survival, but relapsed and refractory cases have very poor outcomes. Nowadays, even with a better understanding of pathogenic pathways, up-front therapy is completely based on chemotherapy and radiotherapy, and treatment-related mortality is not low. Future strategies targeting signaling pathways and immunotherapy are evolving, but we need to better identify those patients with dismal outcomes in a pre-emptive way. Given the rarity of the disease, international collaborations are urgently needed, and clinical trials are the way to change the future.